Abundance of Alexandrium spesies (dinophyceae) in Kuching Estuaries - Tuan Zuraida, binti Tuan Hussin (Universiti Malaysia Sarawak, (UNIMAS), 2012)
A study was carried out to determine the abundance of Alexandrium species that found in two estuaries of Kuching, Samariang Batu and Santubong and the possible environmental parameters that affect the abundance of species. Water samples were collected fortnightly for 12 samplings using Van Dom sampler. Cell enumeration and identification was carried out by using Sedgwick rafter counting chamber under light microscope. The result showed that the abundance of dinoflagellates (Alexandrium spp.) increased with the increasing macronutrient in the water and affected by environmental factors such as salinity, pH and also temperature. Abundance of Alexandrium spp. was relatively low « 300) cell/L throughout the sampling period. Further study on dinoflagellates especially on Alexandrium sp. of other estuaries is important to reaffirm the finding of this study.